2020
DOI: 10.1016/j.jhsg.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Call to Arms: Emergency Hand and Upper-Extremity Operations During the COVID-19 Pandemic

Abstract: Limited data exist regarding volumetric trends and management of upper-extremity emergencies during periods of social restriction and duress, such as the coronavirus disease 2019 pandemic. We sought to study the effect of shelter-in-place orders on emergent operative upper-extremity surgery. Methods: All patients undergoing emergent and time-sensitive operations to the finger(s), hand, wrist, and forearm were tracked over an equal number of days before and after shelter-in-place orders at 2 geographically dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 20 publications
(13 reference statements)
1
27
0
Order By: Relevance
“…These findings were similar to other studies from European countries 8,9 . Contrary to other descriptions, another study demonstrated significant increase in the number of hand and wrist injuries requiring operative management 10 . Interestingly, none of the cited studies detailed the adjustment in presentation patterns or correlations with the behavioural changes resulting from the imposed lockdown measures.…”
Section: Introductionsupporting
confidence: 82%
“…These findings were similar to other studies from European countries 8,9 . Contrary to other descriptions, another study demonstrated significant increase in the number of hand and wrist injuries requiring operative management 10 . Interestingly, none of the cited studies detailed the adjustment in presentation patterns or correlations with the behavioural changes resulting from the imposed lockdown measures.…”
Section: Introductionsupporting
confidence: 82%
“…During lockdown a reported increase in injuries from deliberate self-harm (DSH) was found in Paris (2.9% v 2.0%), 19 the UK, 38 , 49 Australia 47 , 50 and the US. 40 , 52 A large reduction was reported in diamond et al‘s US centre 29 (0 v 8%), with a milder reduction in Murphy et al‘s UK centre 54 (0.2% v 1%, p = 1.0). In the US Sherman et al reported an increase in the rate of non-accidental injury (NAI) during the pandemic, 55 and an increase in domestic violence was observed in Rhode's centre.…”
Section: Resultsmentioning
confidence: 88%
“…The mean age was reported for 3236 patients and was 43.7 years. 13 , 18 , 19 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 An average of 54.8% were male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations